2007
DOI: 10.5005/jcdp-8-5-1
|View full text |Cite
|
Sign up to set email alerts
|

An Anticalculus Dentifrice with Sodium Hexametaphosphate and Stannous Fluoride: A Six-month Study of Efficacy

Abstract: Aim:To compare the anticalculus efficacy of an experimental dentifrice (0.454% stabilized stannous fluoride/ sodium hexametaphosphate) with a negative control. Methods and Materials:This was a randomized, examiner-blind, parallel group study. After a three-month run-in, qualifying subjects were randomized to the experimental or control dentifrice to use twice a day for six months. Volpe-Manhold Index (V-MI) and oral soft tissue examinations were conducted at baseline, three, and six months. Additional analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The test toothpaste in both studies was 0.454% SnF 2 + SHMP. One study used a positive control (0.243% NaF +0.3% triclosan; [36], and one a negative (0.243% NaF; [37]. After 6 months, the Volpe-Manhold Calculus Index showed 55%–56% lower values for the test toothpaste than either of the positive or negative controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test toothpaste in both studies was 0.454% SnF 2 + SHMP. One study used a positive control (0.243% NaF +0.3% triclosan; [36], and one a negative (0.243% NaF; [37]. After 6 months, the Volpe-Manhold Calculus Index showed 55%–56% lower values for the test toothpaste than either of the positive or negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…In the Winston et al. [37] study, home-based and unsupervised use of a SnF 2 dentifrice during normal hygiene procedures effectively inhibited calculus regardless of the baseline levels of calculus. The significant anti-calculus efficacy that was observed is further evidence of the capacity of SHMP to interfere with calculus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Adding an SnF 2 toothpaste to the daily oral care regimen has been shown to have multiple oral health benefits including reduction of dental calculus buildup, dental plaque, gingivitis, staining, and halitosis. A recent systematic review found evidence that significant reduction in calculus formation was produced by a toothpaste containing SnF 2 and a calcium phosphate mineralization inhibitor (SHMP) [ 112 ]. The SnF 2 + SHMP toothpaste also showed to play an important role in stain reduction [ 113 , 114 ].…”
Section: Fluoridesmentioning
confidence: 99%
“…It must be removed with hand, sonic or ultrasonic instruments, procedures which are labor and time consuming and costly. Consequently, there has been considerable interest in formulas, mostly incorporated in dentifrices, containing zinc citrate, chlorohexidine, bisphosphonates, pyrophosphates, triclosan, polymers and copolymers attempting either to inhibit or retard the formation and accumulation of calculus [6][7][8][9][10][11]. These agents appear to reduce the formation of supragingival calculus by 30-50%, the variance probably due to differences in study design [12].…”
Section: Introductionmentioning
confidence: 99%